DIAGNOSIS OF DERMATOMYOSITIS. CLINICAL CASE (International journal of medical sciences, 2025)
The described clinical case is notable for the early diagnosis of dermatomyositis. Timely diagnosis and correct selection of therapy are fundamental to reducing the incidence of various complications and improving the quality of life of patients with this pathology.